Formulation Of Criminal Sanctions Policy Against Drug Crimes At Jayapura Resort Police - Syah, Muhammad Topan; Ingratubun, Junaidi Abdullah (Faculty of Law, Universitas Pekalongan, 2024)
This study aims to determine the application of sanctions against perpetrators of narcotics crimes and what factors hinder law enforcement officers in the context of overcoming narcotics crimes in the jurisdiction of the Jayapura Police. The type of research used is the socio-juridical approach method, namely in addition to studying the law theoretically and normatively in the form of analyzing various laws and regulations, books and articles that have a correlation and are relevant to the problems studied, it will also study the law in its implementation with data collection techniques through interviews and documentation. The results of the study show that the formulation of criminal sanctions against perpetrators of narcotics crimes in positive law is contained in Law Number 35 of 2009 concerning Narcotics in the context of eradicating narcotics crimes regulated in Article 111 - Article 148 and the inhibiting factors of the police in preventing the eradication and handling of narcotics crimes are due to the lack of awareness of the general public about their role in efforts to prevent and eradicate drug abuse, the lack of involvement of elements of society that are actually very strategic, effective and efficient for preventive efforts such as religious leaders, counseling that has been carried out so far in the community, especially teenagers, is lacking, paying attention to the conditions of the targets, drug prevention and rehabilitation programs have not reached rural areas. Therefore, it is necessary to revise the articles in Law Number 35 of 2009 which have legal weaknesses and complicate the law enforcement process; and it is necessary to prepare Indonesian legal instruments that can prevent the entry of organized crime such as narcotics, especially in terms of accommodating modern technology that can be used as a mode of crime.